PENYULUHAN HUKUM TENTANGPIDANA TERHADAP PELAKU PENGANIAYAAN DENGAN RETARDASI MENTAL - Sofian, Sofian; Manurung, Abdul Azis; Dermawan, Ari (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract:Mental retardation is categorized as People with Mental Problems (ODMK) as referred to in Article 1 number 2 of Law Number 18 of 2014 concerning Mental Health, namely people who have physical, mental, social, developmental, and/or quality of life problems who are at risk of experiencing mental disorders. This thesis aims to analyze how criminal liability is applied to perpetrators of criminal acts of abuse who suffer from mental retardation, as well as to re-analyze the basis for the judge's considerations in issuing a verdict against the perpetrator, by referring to Decision Number 817/Pid.B/2024/PN.Kis. This study uses a normative juridical approach method with a descriptive research type. Data were obtained through literature studies by reviewing statutory regulations, legal literature, and court decision documents. The analysis was carried out qualitatively-descriptively against relevant legal norms and concrete case studies. The results of the study indicate that perpetrators of criminal acts of abuse who suffer from mental retardation cannot be fully held criminally responsible if it is proven that their mental condition affects their ability to understand or control their actions as regulated in Article 44 of the Criminal Code. In Case Number 817/Pid.B/2024/PN.Kis, although the defendant was proven to have committed assault according to Article 351 paragraph (1) of the Criminal Code, ideally the medical evidence process related to the defendant's mental condition would be the main basis in the judge's considerations, as well as trial facts to determine the appropriateness of criminal responsibility for the defendant in accordance with the principles of criminal law and protection for people with mental retardation. Keywords: Criminal, Responsibility  Abstrak: Retardasi mental dikategorikan sebagai Orang Dengan Masalah Kejiwaan (ODMK) sebagaimana dimaksud dalam Pasal 1 angka 2 Undang-Undang Nomor 18 Tahun 2014 tentang Kesehatan Jiwa, yaitu orang yang memiliki masalah fisik, mental, sosial, pertumbuhan, dan/atau kualitas hidup yang berisiko mengalami gangguan jiwa. Skripsi ini bertujuan untuk menganalisis bagaimana pertanggungjawaban pidana diterapkan terhadap pelaku tindak pidana penganiayaan yang mengalami retardasi mental, serta menganalisis kembali dasar pertimbangan hakim dalam menjatuhkan putusan terhadap pelaku tersebut, dengan merujuk pada Putusan Nomor 817/Pid.B/2024  /PN.Kis. Penelitian ini menggunakan metode pendekatan yuridis normatif dengan jenis penelitian deskriptif. Data diperoleh melalui studi kepustakaan dengan mengkaji peraturan Perundang-Undangan, literatur hukum, serta dokumen putusan pengadilan. Analisis dilakukan secara kualitatif-deskriptif terhadap norma hukum yang relevan serta studi kasus konkret. Hasil penelitian menunjukkan bahwa pelaku tindak pidana penganiayaan yang menderita retardasi mental tidak dapat sepenuhnya dimintai pertanggungjawaban pidana apabila terbukti bahwa kondisi kejiwaannya memengaruhi kemampuannya memahami atau mengendalikan perbuatannya sebagaimana diatur dalam Pasal 44 KUHP. Dalam Perkara Nomor 817/Pid.B/  2024/PN.Kis, meskipun terdakwa terbukti melakukan penganiayaan sesuai Pasal 351 ayat (1) KUHP, idealnya proses pembuktian medis terkait kondisi kejiwaan terdakwa akan menjadi landasan utama dalam pertimbangan hakim. serta fakta persidangan untuk menentukan kelayakan pertanggungjawaban pidana terhadap terdakwa sesuai prinsip-prinsip hukum pidana dan perlindungan terhadap ODMK. Kata Kunci: Pidana, Pertanggungjawaban